2009
DOI: 10.1021/jp900485p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Photochromic Compounds. 1. Bond Length Alternation and Absorption Spectra for the Open and Closed Forms of 29 Diarylethene Derivatives

Abstract: We apply several exchange-correlation functionals in combination with time-dependent density functional theory to predict the maximum wavelengths in the absorption spectra for 29 diarylethene derivatives in both open and closed isomeric forms. Solvent effects and accurate molecular geometries are found to be important to obtain good agreement with experimental absorption wavelengths. In order to evaluate the quality of geometry optimization, we compare predicted bond length alternation parameters with experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 56 publications
(76 reference statements)
3
47
0
Order By: Relevance
“…Patel and Masunov [114,115] employed TD-DFT with the linear response formalism to include continuum solvation to calculate absorption spectra of 29 diarylethene derivatives. They found that M05-2X gave the most accurate predictions of bond length alternation (see also [116]), and M05 at M05-2X geometries gave the best agreement with experiment for spectral data of both open and closed isomers.…”
Section: Excited Statesmentioning
confidence: 99%
“…Patel and Masunov [114,115] employed TD-DFT with the linear response formalism to include continuum solvation to calculate absorption spectra of 29 diarylethene derivatives. They found that M05-2X gave the most accurate predictions of bond length alternation (see also [116]), and M05 at M05-2X geometries gave the best agreement with experiment for spectral data of both open and closed isomers.…”
Section: Excited Statesmentioning
confidence: 99%
“…6 Simple as it seems, accurately describing BLA is a challenge for many electronic structure methods. Trans-polyacetylene (referred to here as CC-II) is the most intensively studied system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the diarylethene derivatives have attracted much attention due to their potential applications in the future optoelectronic devices, such as highcapacity optical memories and ultrafast switches. [4][5][6] To realize such applications, many theoretical investigations have been carried out for revealing functionalities of the diarylethene derivatives, such as the reaction mechanism on excited states, [7][8][9][10][11][12] UV-vis spectra, [13][14][15][16][17][18][19][20][21] photoswitching of conductance, [22][23][24][25] and twophoton absorption. 26 We have also developed a parameter tuning scheme of density functional theory for reproducing the excitation energies of diarylethene derivatives well, 27,28 and have proposed a novel nonlinear optical property switching using open-shell singlet diarylethene derivatives.…”
Section: Introductionmentioning
confidence: 99%